Workplace Diversity Education as a Catalyst for Employee Engagement and Performance - OLU-OGUNLEYE, Itunu; AKANJI, Babatunde (Journal of Research in Educational Sciences, 2025)
This study is intended to explore workplace diversity education as a driver of employee engagement and performance in selected universities in Ondo State, Nigeria. During times of fast-growing higher education that need to change with regard to globalization and demographic shifts, diversity education can be used as a strategic lever to create an enabling work environment that fosters employees' commitment and productivity. This research had a descriptive survey design targeting academic staff across many universities. In order to attain these data, this study has adopted a structured questionnaire from stratified random samples. Quantitative data were analyzed to get the descriptive statistics, Pearson's correlation, and multiple regression analysis; whereas thematic analysis was done in case of qualitative data. The findings indicated a positive and significant relationship between workplace diversity education and employee engagement, such that the more inclusive the training programs, the higher the job involvement, affective commitment, and discretionary effort. Diversity education also improved employee performance by enhancing teaching effectiveness, research output, and professional collaboration.